Erythrocytes as a source of essential lipids for Treponema hyodysenteriae. - Stanton, T B (1987)
Mammalian erythrocytes were tested as a nutrient source for the spirochete Treponema hyodysenteriae, the etiologic agent of swine dysentery. Brain heart infusion (BHI) broth did not support growth of T. hyodysenteriae B204 or B78. However, BHI broth supplemented with washed bovine erythrocytes, erythrocyte membranes, or cholesterol was an excellent culture medium for these strains (4 X 10(8) to 10(9) cells per ml, final population densities). Small amounts of cholesterol (3 to 10 micrograms/ml of medium) were required for maximum cell yields of strain B204. Of various sterols and sterol-like compounds tested, cholestanol and sitosterol could substitute for cholesterol. BHI-dehydrated medium extracted with CHCl3-CH3OH (2:1, vol/vol) to remove lipids was used to prepare lipid-depleted culture broth. Lipid-depleted broth supplemented only with cholesterol did not support T. hyodysenteriae B204 growth. However, this same broth supplemented either with vesicles made from cholesterol and phosphatidylcholine or with washed erythrocytes was a good culture medium for the spirochete. Thus, both cholesterol and a phospholipid are needed for T. hyodysenteriae growth in lipid-depleted broth. Mammalian erythrocytes can be used by the spirochete as a source of these lipids.